Freedom's currency slavery, capitalism, and self-purchase in the United States - Bernier, Julia Wallace (University of Pennsylvania Press, 2024)
"Freedom's Currency argues that freedom played a central role in the social and economic lives of the enslaved and in the ways that these aspects of their lives overlapped. This intimate portrait of community illuminates the complexity of enslaved people's ideas about their place at the intersection of slavery and American capitalism and their attempts to value freedom above all."
"Revised dissertation"
Keywords: Geschichte; Finanzierung; Abolitionismus; Wirtschaftliche Lage; Sklave; USA; Enslaved persons / United States / Economic conditions; Slavery / Law and legislation / United States / History; Enslaved persons / United States / History; United States / Economic conditions / To 1865; Enslaved Persons; Hochschulschrift